Adaptation of the model of a controlled flight of an airplane in the system of trajectory estimation, forecasting and prevention of conflict situations - Васильєв B. M. (Proceedings of National Aviation University (archive), 2021)
The method and algorithm of identification of the parameters of the model of controlled flight of the aircraft for the system of trajectory estimation of forecasting and prevention of conflict situations is proposed. The computer simulation carried out has converged the estimation process. The application of the method allows to raise the level of adequacy and reliability of decision-making in automated air traffic control systems.